Hermann Hesse and His Critics The Criticism and Bibliography of Half a Century - Mileck, Joseph (UNC Studies in the Germanic Languages and Literatures, 1958)
Originally published in celebration of Hermann Hesse's 80th birthday, this highly documented study, practical handbook, and reference work for Hesse scholarship is presented in three parts. Mileck gives a short biography of Hesse's life and a general characterization of his writing, followed by a critical history of Hesse scholarship through 1957 organized chronologically, categorically and thematically. Finally he presents an exhaustive bibliography containing more than 1800 items of all the works by and about Hesse.